ROOT CAUSE ANALYSIS FOR CONDUCTING UNIVERSITY’S COMMUNITY SERVICE TO MICRO AND SMALL FIRMS - Sri Maryanti; Afred Suci; Nining Sudiar; Hardi Hardi (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2020)
The study aims to identify the root problems facing by the small firm that further can guide the university to implement the most appropriate treatments to enhance the partnering small firm's business performance. A qualitative approach was employed, primarily conducting in-depth interviews and brainstorming with business owners, employees, store managers, and consumers of